1997
DOI: 10.3354/meps159229
|View full text |Cite
|
Sign up to set email alerts
|

Predator deterrence and 2,4-dibromophenol conservation by the enteropneusts Saccoglossus bromophenolosus and Protoglossus graveolens

Abstract: Saccoglossus Dromophenolosc~s I n g et al., 1994 and Protoglossus graveolens Giray & Klng, 1996 contain high concentratlons of 2,4-dibromophenol (DBP), the functlon of whlch is uncertain. Mature enteropneusts that were collected from the field and maintamed in v~tro without bromide retained DBP, which is inconsistent wlth actlve DBP secretion into the burrow env~ronment. DBP was also conserved during field manipulations that decreased food availability in situ. Further, DBP did not deter predation in feeding e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 20 publications
1
23
0
Order By: Relevance
“…Thomas (1972) observed that S. otagoensis (which produces 2,3,4-tribromopyrrole) was unpalatable to fishes, while Giray and King (1997a) found that S. bromophenolosus (which produces 2,4-dibromophenol) was palatable to invertebrate consumers. In our assays, 2,4-dibromophenol did deter feeding, at 5-15ϫ the natural concentration reported for this compound (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Thomas (1972) observed that S. otagoensis (which produces 2,3,4-tribromopyrrole) was unpalatable to fishes, while Giray and King (1997a) found that S. bromophenolosus (which produces 2,4-dibromophenol) was palatable to invertebrate consumers. In our assays, 2,4-dibromophenol did deter feeding, at 5-15ϫ the natural concentration reported for this compound (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, when worms that produce brominated compounds have been exposed to predators, outcomes have been variable. Thomas (1972) and Prezant et al (1981) found the hemichordates Saccoglossus otagoensis and S. kowalevskii (which both produce 2,3,4-tribromopyrrole) were unpalatable to fishes, but Giray and King (1997a) found Saccoglossus bromophenolosus (which produces 2,4 dibromophenol) was palatable to two predatory polychaetes and a hermit crab. In none of the above examples were extracts or specific metabolites tested directly to assess the potential chemical basis of feeding patterns.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Saccoglossus bromophenolosus were collected from the top 15 cm of sediment from Lowes Cove, Maine, USA, in July 2003. This location has been the site of numerous studies on S. bromophenolosus and their natural products (King et al 1994, Giray & King 1997. Approximately 50 worms were preserved in jars containing methanol (~30 ml); 3 whole worms were also frozen directly with liquid nitrogen.…”
Section: Methodsmentioning
confidence: 99%